'To clean the face, wash behind the ears and brush the teeth'. The project to conserve the Norwegian written heritage, 2001 - 04 and its results. - Eide, Elisabeth (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
At the National Library of Norway two major projects, a conservation project and a card conversion project were planned and will by June 2004 be partly completed. This article presents the projects, with the main emphasis on the conservation project, which was my responsibility.